Short-term clinical course of knee pain in children and adolescents: a feasibility study using electronic methods of data collection - Swain, Michael; Henschke, Nicholas (Physiotherapy research international, 2016)
Background and Purpose Musculoskeletal disorders, such as knee pain, are common in children and adolescents, but there is a lack of high quality research that evaluates the clinical course of these conditions. The objective of this study was to evaluate the feasibility of conducting a prospective study of children and adolescents with knee pain using electronic methods of data collection. Methods Children and adolescents with knee pain that presented to primary care physiotherapy clinics were enrolled and followed-up on a weekly basis via short messaging service (SMS) until their knee pain had recovered (i.e. two consecutive weeks of no pain). Feasibility was assessed in terms of recruitment, retention and response rates to SMS and an online questionnaire. Baseline and 6-month follow-up measures included pain, disability, physical function, physical activity and health related quality of life. Kaplan-Meier survival analysis was used to estimate the median time to knee pain recovery. Results Thirty participants (mean age 13.0 ± 2.2 years, 53% boys) were recruited over 26 months. The overall response rate to weekly SMS follow-up was 71.3% (809 received/1135 sent). One third of participants stopped responding to SMS prior to recovery, and these participants typically had a much lower response rate during the time they remained in the study. At 6-month follow-up, 80% of the cohort completed the final online questionnaire, and 29% of participants still reported current knee pain (≥1/10 VAS). The median time for knee pain recovery was 8 weeks (95%CI: 5, 10). Conclusion Electronic data collection alone seems insufficient to track pain recovery in young people and may need to be supplemented with more traditional data collection methods. Researchers should consider further measures to address slow recruitment rates and high attrition when designing large prospective studies of children and adolescents in the future. Copyright © 2016 John Wiley & Sons, Ltd.
First published: 16 May 2016
Gesehen am 20.06.2018